Knowledge, attitudes, and practices of dietary management among patients with rheumatoid arthritis in China - Li, Xueyong; Liu, Ju; Yu, Jie; Dong, Liang (Frontiers in Public Health, 2024)
BackgroundThis study aims to assess the knowledge, attitudes, and practices (KAP) regarding dietary management among patients with rheumatoid arthritis (RA).MethodsA cross-sectional survey was conducted at JiuJiang NO.1 People’s Hospital from November 2023 to May 2024. Data were gathered using structured questionnaires that solicited demographic information and measured KAP scores related to dietary management in RA patients.ResultsThe survey yielded 504 valid questionnaires. Of the respondents, 306 (60.71%) had a Body Mass Index (BMI) within the optimal range of 18.5–23.9 kg/m2. The mean scores for knowledge, attitude, and practice were 10.13 ± 3.58 (possible range: 0–22), 31.38 ± 2.38 (possible range: 9–45), and 4.46 ± 2.30 (possible range: 0–12), respectively. Correlation analysis revealed significant relationships between knowledge and practice (r = 0.294, p < 0.001) as well as between attitude and practice (r = 0.178, p < 0.001). Multivariate logistic regression showed that knowledge score (OR = 1.165, 95% CI: [1.078, 1.259], p < 0.001) was independently associated with proactive practice. The structural equation model (SEM) results showed that knowledge had direct effects on attitude (β = 0.291, p < 0.001) and practice (β = 0.188, p < 0.001). Meanwhile, attitude had a direct impact on practice (β = 0.081, p = 0.045).ConclusionThis study indicates that patients with RA generally demonstrate inadequate knowledge but hold positive attitudes toward dietary management, despite relatively inactive practices in implementing such dietary changes. Healthcare providers should prioritize educational interventions that not only enhance patient understanding but also actively support the implementation of dietary management strategies in clinical settings.